Acute free gallbladder perforation with atypical presentation: a case report - Aldhamdi, Nouf Mohammed A.; Alalqam, Muntadhar; Al Dammad , Kamal (International Surgery Journal, 2025)
Gallbladder perforation (GBP) is a rare but potentially fatal complication of biliary tract disease if left untreated. We report the case of a 90-year-old female who presented with generalized abdominal pain associated with diarrhea and chills for three days. Upon examination, the patient was vitally stable, the abdomen was distended with epigastric and right hypochondriac tenderness, and she was positive for Murphy's sign. Laboratory findings showed high levels of liver enzymes, but normal bilirubin levels. Abdominal computed tomography revealed a gangrenous and perforated GB with marked inflammation and free fluid in the pelvis, right para-colic gutter, and GB bed. The patient was managed with intravenous antibiotics and laparoscopic cholecystectomy was successfully performed. The patient had an uneventful postoperative course. The diagnosis of GBP can be easily missed until it is detected intraoperatively because no clinical signs or pathognomonic features suggest the condition. Therefore, a high level of intuition is necessary to promptly establish a diagnosis, particularly in elderly patients. The approach to GBP remains an area of debate, considering many factors, including patient's stability, facility, and surgeon's expertise. Laparoscopic cholecystectomy should be considered as the first line of management in GBP cases, depending on the patient's stability and the surgeon's skills.